Improvement of the Quality of Water Purification from Hydrocarbons Using the Fibers from Recycled Thermoplastics; IOP Conference Series: Materials Science and Engineering; Vol. 132 : Modern Technologies for Non-Destructive Testing - Galtseva (Gal’tseva) O. V. Olga Valerievna; Bordunov S. V.; Natalinova N. M. Nataliya Mikhailovna; Mazikov S .V. (2016, 2016)
Title screen